Vzdělávací potřeby ředitelů na různých stupních škol - Svobodová, Dana (Univerzita Karlova, Pedagogická fakulta, 2016)
Závěrečná diplomová práce se zabývá vzděláváním ředitelů škol. Konkrétně vzdělávacími potřeby ředitelů na středních, základních a mateřských školách. Cílem práce je zjištění rozdílů vzdělávacích potřeb ředitelů na různých stupních škol a jejich vzájemná komparace. Teoretická část uvádí východiska pro zjištění a komparaci vzdělávacích potřeb. Vzdělávací potřeby jsou v této práci zjišťovány pomocí Kompetenčního modelu ředitele školy. Ředitelé uváděných stupňů škol stanovují požadovaný stav dílčích kompetencí a hodnotí vlastní skutečný stav. Ředitelé mají také možnost sami určit vlastní vzdělávací potřeby a dát doporučení jakožto doplnění současné vzdělávací nabídky. Výzkumné šetření bylo realizováno metodou dotazníku. Touto prací došlo k zjištění, že vzdělávací potřeby ředitelů středních škol se výrazně liší od vzdělávacích potřeb ředitelů škol základních a mateřských. Ředitelé základních a mateřských škol mají vzdělávací potřeby shodné. Práce přináší konkrétní východiska pro stanovení vzdělávací nabídky pro ředitele jednotlivých stupňů škol, a to i s návrhy jejího obohacení. The master's thesis "Educational needs of headmasters at various school levels" deals with education of headmasters of various school levels. In particular, it deals with educational needs of headmasters at kindergartens, primary schools and secondary schools. The aim of the thesis is to find differences among educational needs of headmasters of various school levels and its mutual comparison. Theoretical part works with resources for identifying and comparison of educational needs. Those educational needs are in this thesis identified through "Competency model of the headmaster of the school". Headmasters of mentioned school levels specify required level of partial competencies and evaluate its real situation. Headmasters also have the possibility to bring their own proposal for type of educational need and provide also their recommendation for supplementation of current offer in the field of education. Research was realized through the form of questionnaire. Findings of the research brought, that educational needs of headmasters of secondary schools differ a lot from needs of headmasters of kindergartens and primary schools. Headmasters of primary schools and kindergartens state the same educational needs. The thesis brings very particular bases for creating educational offer for headmasters of. Centrum školského managementu Pedagogická fakulta Faculty of Education